Transcriptomic insight into the hybridization mechanism of the Tambacu, a hybrid from Colossoma macropomum (Tambaqui) and Piaractus mesopotamicus (Pacu) - Mareco, Edson Assunção; de la Serrana, Daniel Garcia; de Paula, Tassiana Gutierrez [UNESP]; Zanella, Bruna Tereza Thomazini [UNESP]; da Silva Duran, Bruno Oliveira [UNESP]; Salomão, Rondinelle Artur Simões; de Almeida Fantinatti, Bruno Evaristo [UNESP]; de Oliveira, Victor Hugo Garcia; dos Santos, Vander Bruno; Carvalho, Robson Francisco [UNESP]; Dal-Pai-Silva, Maeli [UNESP] (Elsevier, 2023)
Interspecific hybrids are highly complex organisms, especially considering aspects related to the organization of genetic material. The diversity of possibilities created by the genetic combination between different species makes it difficult to establish a large-scale analysis methodology. An example of this complexity is Tambacu, an interspecific hybrid of Colossoma macropomum (Tambaqui) and Piaractus mesopotamicus (Pacu). Either genotype represents an essential role in South American aquaculture. However, despite this importance, the genetic information for these genotypes is still highly scarce in specialized databases. Using RNA-Seq analysis, we characterized the transcriptome of white muscle from Pacu, Tambaqui, and their interspecific hybrid (Tambacu). The sequencing process allowed us to obtain a significant number of reads (approximately 53 billion short reads). A total of annotated contigs were 37,285, 96,738, and 158,709 for Pacu, Tambaqui, and Tambacu. After that, we performed a comparative analysis of the transcriptome of the three genotypes, where we evaluated the differential expression (Tambacu vs Pacu = 11,156, and Tambacu vs Tambaqui = 876) profile of the transcript and the degree of similarity between the nucleotide sequences between the genotypes. We assessed the intensity and pattern of expression across genotypes using differential expression information. Clusterization analysis showed a closer relationship between Tambaqui and Tambacu. Furthermore, digital differential expression analysis selected some target genes related to essential cellular processes to evaluate and validate the expression through the RT-qPCR. The RT-qPCR analysis demonstrated significantly (p < 0.05) elevated expression of the mafbx, foxo1a, and rgcc genes in the hybrid compared to the parents. Likewise, we can observe genes significantly more expressed in Pacu (mtco1 and mylpfa) and mtco2 in Tambaqui. Our results showed that the phenotype presented by Tambacu might be associated with changes in the gene expression profile and not necessarily with an increase in gene variability. Thus, the molecular mechanisms underlying these “hybrid effects” may be related to additive and, in some cases, dominant regulatory interactions between parental alleles that act directly on gene regulation in the hybrid transcripts.
Keywords: Aquaculture; mRNA expression; Muscle growth; RNA-Seq; Skeletal muscle; Teleost fish